2003
DOI: 10.1034/j.1398-9995.2003.00112.x
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of atopic dermatitis in Italian schoolchildren

Abstract: The prevalence of doctor-diagnosed AD in Italian schoolchildren is comparable to those reported for other developed countries. Family history of atopy was the single most important associated factor, while the complex interplay of environmental factors remains to be elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 46 publications
6
56
1
4
Order By: Relevance
“…Também não foi relatada associação entre peso ao nascer e rinite alérgica ou dermatite atópica em crianças italianas de 9 anos de idade 23 , nem em uma coorte de adolescentes da Nova Zelândia 4 . Leadbitter et al 7 tampouco encontraram associação entre essas variáveis.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Também não foi relatada associação entre peso ao nascer e rinite alérgica ou dermatite atópica em crianças italianas de 9 anos de idade 23 , nem em uma coorte de adolescentes da Nova Zelândia 4 . Leadbitter et al 7 tampouco encontraram associação entre essas variáveis.…”
Section: Resultsunclassified
“…[23][24][25] anos, com base em uma lista de nomes de participantes previamente projetada e sorteada a partir dos bancos de dados descritos acima. A seleção foi realizada com base na caracterização geoeconômica da cidade, que é constituída de quatro regiões geográficas definidas pela renda do chefe da família e classificadas como "pobre", "média-baixa", mé-dia-alta" e "rica" 14 .…”
Section: Introductionunclassified
“…Park et al 12 reported that the incidence of nipple eczema was 6.2% in Korean atopic dermatitis patients above 12 years old. However, the incidence of nipple eczema is much lower in Western atopic dermatitis patients 13 . This may explain why no reports of CCA on the nipple area are from Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that one of the main risk factors for the development of allergic diseases is heredity [14][15][16]. By previous survey in Vilnius, it was found, that there were 2 times more allergic children in families with allergic members in comparison with families in which no one had allergy [17].…”
Section: Discussionmentioning
confidence: 99%